npj Vaccines - Titball, Richard; Rupp, Richard; Messling, Veronika; Barrett, Alan.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Vaccines considers all aspects of research covering the development of human and veterinary vaccines. The journal covers a broad range of topics including but not limited to: Vaccine development and design Vaccine immunology and mechanisms of action Vaccine adjuvants and delivery systems Vaccine safety and efficacy evaluation Vaccine production and manufacturing Vaccine hesitancy and acceptance Vaccines for emerging infectious diseases One Health approaches to vaccination Vaccines for non-infectious diseases, including cancer vaccines, and against chronic conditions, autoimmune diseases, allergies, and non-communicable diseases Veterinary vaccines for animal health Vaccine policy, regulation, and access The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by vaccine experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Medical microbiology; Virology; Public health; Pharmacology; Diseases; Biomedical Research; Medical Microbiology; Virology; Public Health; Pharmacology; Diseases